2010
DOI: 10.1021/am100786z
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes of Silica Mesocellular Foam Supported Amine-Functionalized CO2 Adsorbents Upon Exposure to Steam

Abstract: Three classes of amine-functionalized mesocellular foam (MCF) materials are prepared and evaluated as CO(2) adsorbents. The stability of the adsorbents under steam/air and steam/nitrogen conditions is investigated using a Parr autoclave reactor to simulate, in an accelerated manner, the exposure that such adsorbents will see under steam stripping regeneration conditions at various temperatures. The CO(2) capacity and organic content of all adsorbents decrease after steam treatment under both steam/air and stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
204
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(219 citation statements)
references
References 75 publications
9
204
1
3
Order By: Relevance
“…PEI-SBA-15 and DMA-SBA-15 were prepared according to the previous reports. [27,28] Characterization: Powder XRD patterns were collected on an M03X-HF (Bruker AXS) with Cu Ka radiation. Fourier transform infrared (FT-IR) spectroscopy was performed by using a Magna-IR 560 (Nicolet Instrument).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PEI-SBA-15 and DMA-SBA-15 were prepared according to the previous reports. [27,28] Characterization: Powder XRD patterns were collected on an M03X-HF (Bruker AXS) with Cu Ka radiation. Fourier transform infrared (FT-IR) spectroscopy was performed by using a Magna-IR 560 (Nicolet Instrument).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, this class of amine adsorbents has been shown to be stable over hundreds of cycles in humid conditions, [23] although other recent results showed that such materials were less stable than class 1 adsorbents upon exposure to steam. [27,28] The disadvantage of class 2 adsorbents is that they often contain a smaller amount of amines than other classes. Combining the advantages of the aforementioned classes of materials, Jones and co-workers reported the first study of class 3 materials for CO 2 capture.…”
mentioning
confidence: 99%
“…Silica-and alumina-supported amine adsorbents were synthesized according to procedures reported in previous papers from our group [25,26]. A commercial silica support (PD-09024 from PQ Corporation) as well as laboratory prepared SBA-15 [27] and γ-alumina [25] were used as support materials.…”
Section: Materials Synthesismentioning
confidence: 99%
“…Thus, it is essential to control the morphology of MCF materials to extend their industrial applications. Nowadays, the MCF-type catalysts are at he research hotspot owing to their potential utilizations, for example, catalysis, [42] adsorption, [43] separation, [41] and enzymei mmobilization. [39] However,t ot he besto f our knowledge,t here are almost no reports on the application of MCF-type catalysts in the hydrotreatment process of heavy oil reactionw ith large molecules, for example, the HDS reactions of DBT and alkyl-substituted dibenzothiophene derivatives.…”
mentioning
confidence: 99%